Timely access to care in the treatment of rectal cancer and the effect on quality of life. (2nd February 2018) - Walming, S.; Block, M.; Bock, D.; Angenete, E.
Abstract: Aim: The aim of this study was to investigate if a delay in a patient's first contact with a healthcare professional, and any subsequent delay in diagnosis, affected self‐assessed quality of life prior to start of treatment for rectal cancer. Method: Questionnaires were administered when patients had been informed of the diagnosis and planned treatment. The primary end‐point was self‐assessed quality of life according to a seven‐point Likert scale. The response variables were dichotomized and analysed by unadjusted and adjusted binary logistic regression. Results: A reported duration of symptoms longer than 4 months was found to be associated with a lower quality of life than a reported duration of symptoms of less than 3 months. Furthermore, a reported period of longer than 2 months from first contact with a healthcare professional to a diagnosis was found to correlate with lower quality of life compared with a period shorter than 2 months. However, when adjusting for possible confounding variables the duration of symptoms and time to diagnosis were not found to affect self‐assessed quality of life. Several variables were found to have significant influence in the statistical model, including sense of coherence, the presence of negative intrusive thoughts, comorbidity, depressed mood, male sex and comorbidity. Conclusion: One conclusion of our study is that further efforts to shorten delay in rectal cancer care with the aim of improving quality of life may be futile. To improve the patient's quality of life at diagnosis other interventions should be considered, such as screening for depression and/or negative intrusive thoughts.